Pouring good money after bad: a comparison of Asian and Developed country managerial decision-making in sunk cost situations in financial institutions - Khan, Basir A.; Sharp, David J.; Salter, Stephen B. (2000)
Recent currency and bond trading losses at Barings and Daiwa banks illustrate the willingness of managers to over-commit resources to a course of action in which sunk costs have been incurred and which by any rational standards should have been long discontinued. An international study of the determinants of managerial risk-taking is important because it sheds light on the extent to which aggressive decision-making reported in North American literature is prevalent elsewhere, and whether there are systematic differences between behaviours in different countries. The study has important implications for the practice of management. For example, by knowing cross-cultural differences in willingness to take risk, and to act in one's individual rather than the general interest, managers in transnational corporations would be better able to predict risk-taking behaviours and adjust internal risk management systems accordingly. - Reproduced
Keywords: Financial institutions; Decision making